Latin America towards the new millennium: perspectives for sustainable development - Castro V., Gonzalo (1997)
After the lost decade of the 1980s, the 1990s represent the "decade of hope" for Latin America. A vigorous economic transformation is reducing the role of the state and allowing the private sector to become once again the main engine of development. What is the relation between this growing role of the private sector and the increasingly important need to conserve the environment?   This article explores this relation and establishes that a healthy environment is the foundation over which long-term sustainable development can be built. Furthermore, given the very rich natural resources and environmental characteristics of the region, the main comparative advantages over which prosperous Latin America societies can be built must consider these ecological riches. The beginning of the third millennium provides an excellent opportunity for this paradigm shift to occur.